Diabetes and pulmonary tuberculosis: a global overview with special focus on the situation in Asian countries with high TB-DM burden - Chunlan Zheng; Minhui Hu; Feng Gao (Taylor & Francis Group, 2017)
Background: The double burden of tuberculosis (TB) and diabetes mellitus (DM) is hitting certain Asian countries harder than other areas. In a global estimate, 15% of all TB cases could be attributable to DM, with 40% of those cases coming from India and China. Many other countries of South, East, and South-East Asia are of particular concern given their TB burdens, large projected increases in DM prevalence, and population size. Objective: In this narrative review, we aimed to: (i) give an overall insight into the evidence on TB-DM epidemiology from high double burden Asian countries, (ii) present the evidence on bi-directional screening implementation in this region, (iii) discuss possible factors related to higher TB susceptibility of Asian diabetic patients, and (iv) identify TB-DM comorbidity treatment challenges. Methods: The PubMed and Google Scholar databases were searched for all studies addressing DM/TB epidemiology, bi-directional screening and management in South, East and South-East Asia. Results: We identified the DM prevalences among TB patients as ranging from approximately 5% to more than 50%, whereas TB prevalences among diabetic patients were 1.8-9.5 times higher than in the general population in developing Asian countries. Evidence from studies designed to address diagnosis and treatment of the dual disease in these critical regions is scarce as well as the evidence related to possible DM patients' genetic and acquired predisposition for TB. Conclusion: More prospective studies specifically designed to address adequate screening techniques, identify patients at risk, and define an adequate treatment of dual disease in this region are needed without delay.